Dispersion and gelation properties of alumina systems with Isobam assisted by dicarboxylic acids. Issue 9 (15th June 2019) - Lu, Yuju; Gan, Ke; Xu, Jie; Lv, Lin; Huo, Wenlong; Liu, Jingjing; Zhang, Xiaoyan; Yang, Jinlong
Abstract: Isobam, a copolymer of isobutylene and maleic anhydride, is a newly developed gelling agent for ceramic colloidal forming. However, the Isobam system exposes a weakness of high viscosity when solids loading exceeds 54 vol%. Suitable additives to effectively decrease viscosity and have minimal impact on gelation strength were discovered from various dicarboxylic acids through investigation on zeta potential, viscosity of suspensions, shear modulus during gelation and yield stress and modulus of elasticity of wet green bodies. Alumina ceramics with flexural strength of 442 ± 49 MPa and a Weibull modulus of 10.8 were produced from 54 vol% suspensions with 0.5 wt% Isobam assisted by 0.04 wt% phthalic acid and 0.03 wt% oxalic acid after pressureless sintering.